Implementasi Hukum Tidak Menghadiri Undangan Walimah dengan Sengaja ditinjau dari Mazhab Syafi’i (Studi Kasus Desa Kebun Sayur Batu Bara) - Nurul Hidayah, Erika; Wanto, Sugeng (Universitas Ekasakti, 2023)
This research aims to find out the Islamic law that lives in society and the community's response to Islamic law in the Batu Bara Sayur Garden Village. The method used in this research is field research which is used to collect information through interviews with a number of elements of society and through field observations. According to the Shafi'i School, everyone who is invited is obliged to attend the invitation, but the invitation will be void if there is an excuse. However, in the village of Batu Bara Vegetable Gardens, attending a walimah's invitation is considered a normal thing, when they are invited they don't seem to care and don't give a clear reason why they don't attend the walimah's invitation. When attending a walimah invitation, you also need to look at the terms and criteria regarding whether or not the walimah is required to attend. The results of this research show that the implementation of the law of not attending a walimah's invitation intentionally is a sinful act, because according to the Syafi'i School of Law, attending a Walimah's invitation is fardhu 'ain, and this is not practiced and implemented properly by the Batu Bara Vegetable Garden Village Community.